Pengaruh Media Animal Fun Terhadap Pemahaman Perkembangbiakan Hewan Pada Siswa Tunagrahita Kelas VII SMPLB di SLB G Daya Ananda - Muti Sastia; Yulian Agus Suminar (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The aim of this study was to determine the effect of Animal Fun media on the understanding of animal reproduction concepts in Grade VII students with intellectual disabilities. The research was conducted using a quantitative approach through a Single Subject Research (SSR) method with an A-B-A design. The subject of this study was a student with an intellectual disability who had difficulty identifying the differences between oviparous and viviparous animals and their characteristics. Data were collected by measuring the student’s understanding scores in each phase: baseline 1 (A1), intervention (B), and baseline 2 (A2). Data analysis was carried out using descriptive statistics through visual analysis within and between conditions. The intervention was conducted using Animal Fun media, a visually interactive learning tool designed for students with special needs. The results showed an increase in the student's understanding scores from phase A1 to phase B, and this improvement tended to persist in phase A2. These findings indicate that Animal Fun media had a positive effect on improving the understanding of animal reproduction in students with intellectual disabilities.